2013
DOI: 10.1089/brain.2012.0106
|View full text |Cite
|
Sign up to set email alerts
|

Growing Trees in Child Brains: Graph Theoretical Analysis of Electroencephalography-Derived Minimum Spanning Tree in 5- and 7-Year-Old Children Reflects Brain Maturation

Abstract: The child brain is a small-world network, which is hypothesized to change toward more ordered configurations with development. In graph theoretical studies, comparing network topologies under different conditions remains a critical point. Constructing a minimum spanning tree (MST) might present a solution, since it does not require setting a threshold and uses a fixed number of nodes and edges. In this study, the MST method is introduced to examine developmental changes in functional brain network topology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
187
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(199 citation statements)
references
References 70 publications
12
187
0
Order By: Relevance
“…As far as we know this was the first time for this method to be used for the depression disease. In a previous study, it suggested that more random networks showed low clustering and a short path length, corresponding to MSTs' shorter diameters and higher leaf numbers [40]. Our finding that leaf fraction of the MDD group was higher than the healthy group indicated a shift toward randomization in the brain networks of the MDD group.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As far as we know this was the first time for this method to be used for the depression disease. In a previous study, it suggested that more random networks showed low clustering and a short path length, corresponding to MSTs' shorter diameters and higher leaf numbers [40]. Our finding that leaf fraction of the MDD group was higher than the healthy group indicated a shift toward randomization in the brain networks of the MDD group.…”
Section: Discussionsupporting
confidence: 48%
“…MST appeared in a variety of studies. MST was used as an elegant and sensitive method to capture subtle developmental organization changes in the brain networks of children [40]. In a study of Multiple Sclerosis, findings indicate that MST network analyses were able to detect network changes in the Multiple Sclerosis (MS) patients [41].…”
Section: Complexitymentioning
confidence: 99%
“…In the study of Boersma et al, eyes-closed resting state 14 channel EEGs recorded in 227 children at age 5, with a second recording two years later, were analysed with the synchronization likelihood, a measure of generalized synchronization (Boersma et al, 2013). In the alpha band a number of significant changes in MST measures was found.…”
Section: More Extensive Characterization Of the Mst In Eeg Studiesmentioning
confidence: 99%
“…In this particular study both the raw functional connectivity as well as the beta band MST measures were more sensitive than the weighted normalised clustering coefficient and path length. Compared to the study of Boersma et al (Boersma et al, 2013), a strength was the use of the PLI, which is less sensitive to confounding effects of volume conduction and active reference electrodes compared to the synchronization likelihood. This study suggests that network analysis based upon the MST might be a candidate for the development of brain computer interfaces.…”
Section: More Extensive Characterization Of the Mst In Eeg Studiesmentioning
confidence: 99%
“…Recent studies have provided very useful tools to measure graph based network properties where spatial features may be extracted with post hoc, data-driven analysis of connectivity clusters. The latter approach has recently gained wide interest in neurophysiological studies of all age groups and in various neurocognitive disorders (Boersma et al, 2013;de Haan et al, 2009;Kim et al, 2013;Omidvarnia et al, 2014;Reijneveld et al, 2007).…”
Section: Spatial Blurring Of Scalp Eeg Signals Due To Positioning Inamentioning
confidence: 99%